ENSURING UNITY OF PHYSICAL AND MILITARY-PATRIOTIC EDUCATION OF HIGH SCHOOL STUDENTS IN THE PROCESS OF PHYSICAL СULTURE AND HEALTH-IMPROVING ACTIVITIES - Tymchyk, Mykola; Natalia, Kasich (Theoretical and Methodical Problems of Children and Youth Education, 2023)
The purpose of the research is to justify the methodology of ensuring the unity of physical and military-patriotic education of high school students in the process of physical culture and health-improving activities. According to the aim, the following tasks are solved: clarifying the methodology and finding new content for ensuring the unity of physical and military-patriotic education of high school students in the process of physical culture and health-improving activities. To achieve the goal and solve the research tasks, a set of the following methods was used: theoretical (analysis, systematization of scientific sources on physical and military-patriotic education), empirical (questionnaire, conversation, interview, direct and indirect observation, method of incomplete sentences), pedagogical experiment, and statistical (methods of mathematical statistics). The article reveals the methodology of ensuring the unity of physical and military-patriotic education of high school students in the process of physical culture and health-improving activities. The methods, forms, content and types of physical and military-patriotic education of high school students in physical culture and health-improving activities are highlighted, namely: methods (group interactive lectures and seminars, conversations, assignment, intellectual games and competitions, personal example, pedagogical requirements, encouragement, practicing in behaviour, creating a successful situation at classes of physical culture and health-improving activities, military-applied and physical training; forms (individual, independent, group work with high school students in the process of physical culture and health-improving activities, military-applied and physical training; involvement of participants in extracurricular and out-of-school educational process); content and types (using updated content on military-applied and physical training in lessons of “Defense of Ukraine” and physical culture; a set of military-patriotic and military-sports games, types of physical and health-improving activities). The criteria and indicators of military-patriotic education of high school students in the process of physical culture and health-improving activities are determined, namely: cognitive criterion “knowledge about the unity of physical and military-patriotic education”, emotional-value criterion “desire to express patriotism, military-patriotic education in the process of physical culture and health-improving activities”, voluntary impulse “willingness to express patriotism, military-patriotic education in the process of physical culture and health-improving activities”, activity-practical “ability to express patriotism, military-patriotic education in the process of physical culture and health-improving activities”. It is verified that physical culture and health-improving activities, military-applied and physical training effectively ensure the unity of high school students’ physical and military-patriotic education. The results of the formative stage of the experiment indicated significant positive changes in the levels of military-patriotic education of high school students in the process of physical culture and health-improving activities.